NUMERICAL ANALYSIS OF SHEAR CAPACITY OF DOUBLE CORRUGATED WEB GIRDER INFILLED - Mahzumah, Cindy; Kristijanto, Heppy; Habieb, Ahmad Basshofi; Ghifari, Fikri (Institut Teknologi Sepuluh Nopember, 2025)
This research investigates the shear capacity of double corrugated web steel I- girders filled with concrete using finite element analysis. The study examines the influence of the corrugation angle and the thickness of the concrete filling on the strength capacity of the girder beams. Four beams were designed to fail in shear along a 1500 mm span from the left support of the beam, enabling the determination of shear failure conditions. Each beam had identical properties with a flange width (B) of 250 mm, a web height (H) of 1000 mm, a span length of 3500 mm, a flange thickness (tf) of 15 mm, and a web thickness (tw) of 1 mm. The research employed a 3-point bending method, applying a single load point 1500 mm from the left support. The tests were conducted by varying the corrugation angles and the thickness of the concrete filling in the corrugated web, which served as the research variables. The study aimed to determine the peak load-deflection curve, the failure mode diagram, and the shear capacity of the girder beams. The results of the tests showed that the double corrugated web steel I-girder filled with concrete, with a corrugation angle of 45 degrees and a concrete thickness of 65 mm, exhibited the best load-bearing strength among the three variations tested. It demonstrated a 52.65% increase in load capacity and a 53.49% reduction in deflection compared to the finite element validation test values. In contrast, the other three variations showed a decrease in shear strength.